1993
DOI: 10.1073/pnas.90.11.4991
|View full text |Cite
|
Sign up to set email alerts
|

Maturation stage and proliferation-dependent expression of dUTPase in human T cells.

Abstract: We have developed a database of lymphoid polypeptides detected by two-dimensional polyacrylamide gel electrophoresis to aid in studies of leukemogenesis and of mutation affecting protein structure. In prior studies, we observed a 19-kDa phosphopolypeptide which was induced with proliferation in mature T cells and constitutively expressed in immature thymocytes. In this report we describe the identififcation of this polypeptide as the phosphorylated form of dUTPase (EC 3.6.1.23), following cDNA cloning of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…dUTPase in mitochondria is necessary for integrity of mitochondrial DNA that replicates independently from the cell cycle. In mature lymphocytes, correlation between dUTPase presence and cell mitogenic status suggested enzyme up-regulation in stages associated with DNA synthesis, whereas in immature populations, enzyme levels are constitutive (3). The requirement of actively dividing cells for high dUTPase levels is also confirmed by studies in rat liver regeneration (4) and mitogen-activated T and B cells (5).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…dUTPase in mitochondria is necessary for integrity of mitochondrial DNA that replicates independently from the cell cycle. In mature lymphocytes, correlation between dUTPase presence and cell mitogenic status suggested enzyme up-regulation in stages associated with DNA synthesis, whereas in immature populations, enzyme levels are constitutive (3). The requirement of actively dividing cells for high dUTPase levels is also confirmed by studies in rat liver regeneration (4) and mitogen-activated T and B cells (5).…”
supporting
confidence: 52%
“…However, several fractions of S2 cell extract modulated the activity of recombinant Drosophila dUTPase strictly, depending on the presence of the unique C terminus. 3 This unique region may therefore mediate regulation of dUTPase activity by other protein factors. dUTPases from various organisms contain species-specific, flexible N-or C-terminal extensions that provide interaction surface for cellular macromolecules (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Strahler and co-workers demonstrated that, upon peripheral blood lymphocyte stimulation, there is a large induction of the phosphorylated form of dUTPase. This induction of dUTPase protein coincided with the onset of DNA replication, suggesting a link between dUTPase phosphorylation and the proliferation status of the cell (4).…”
mentioning
confidence: 99%
“…In an attempt to understand and explain our results, we found in previously published work that the expression of cellular dUTPase is regulated by the cell cycle and is at higher levels in dividing cells than in non-dividing cells (Pardo & Gutierrez, 1990;Strahler et al, 1993). In the context of virus infection, uracil incorporation controlled by the expression of cellular dUTPase and enzymes related to dTTP biosynthesis could work as a weapon against viruses (Priet et al, 2006).…”
Section: Discussionmentioning
confidence: 89%